Molecular Analysis Of Salmonella Enterica Serovar Typhi Isolates Using Pulsed-Field Gel Electrophoresis; Comparison Between Acute And Carriers Of Typhoid Fever - Kamaruzzaman, Nor Fadhilah (2011)
Typhoid fever is a systemic disease caused by S.Typhi, a Gram negative bacterium that infects exclusively humans. The disease is endemic in Kelantan, which has the highest incidence in Malaysia. Despite the endemicity, not much information is known regarding the type of S.Typhi strains and its distribution in this region. Thus, this study was conducted to ascertain retrospectively the genetic diversity and distribution of S.Typhi strains isolated from patients with acute typhoid, asymptomatic carriers and environmental samples in Kelantan, between the year 2002 and 2009.